Comparison of the FitroDyne and GymAware Rotary Encoders for Quantifying Peak and Mean Velocity During Traditional Multijointed Exercises. Issue 6 (June 2021) - Fernandes, John F.T.; Lamb, Kevin L.; Clark, Cain C.T.; Moran, Jason; Drury, Ben; Garcia-Ramos, Amador; Twist, Craig
Abstract : Abstract: Fernandes, JFT, Lamb, KL, Clark, CCT, Moran, J, Drury, B, Garcia-Ramos, A, and Twist, C. Comparison of the FitroDyne and GymAware rotary encoders for quantifying peak and mean velocity during traditional multijointed exercises. J Strength Cond Res 35(6): 1760–1765, 2021—The FitroDyne and GymAware rotary encoders are being increasingly used in resistance training to monitor movement velocity, but how closely their velocity outcomes agree is unknown. Consequently, this study aimed to determine the level of agreement between the FitroDyne and GymAware for the assessment of movement velocity in 3 resistance training exercises. Fifteen men performed 3 repetitions of bench press, back squat, and bent-over-row exercises at 10% 1 repetition maximum increments (from 20 to 80%). For each repetition, the FitroDyne and GymAware recorded peak and mean barbell velocity (cm·s −1 ). Although strongly correlated ( r = 0.79–1.00), peak velocity values for the GymAware were significantly lower than the FitroDyne for all exercises and loads. Importantly, the random errors between the devices, quantified through Bland and Altman's 95% limits of agreement, were unacceptable, ranging from ±3.8 to 25.9 cm·s −1 . Differences in mean velocity were smaller (and nonsignificant for most comparisons) and highly correlated ( r = 0.86–1.00) between devices. Notwithstanding smaller random errors than for the peak values, mean values still reflected poor agreement (random errors between ±2.1 and 12.0 cm·s −1 ). These findings suggest that the FitroDyne and GymAware cannot record peak or mean velocity with acceptable agreement and should neither be used interchangeably nor their data compared.